Hospital Competition and Unplanned Readmission: Evidence from a Systematic Review - Jiang Q; Tian F; Liu Z; Pan J (Dove Medical Press, 2021)
Qingling Jiang,1,2 Fan Tian,1,2 Zhenmi Liu,2,3 Jay Pan1,2 1Department of Epidemiology and Health Statistics, West China School of Public Health and West China Fourth Hospital, Sichuan University, Chengdu, Sichuan Province, People’s Republic of China; 2Institute for Healthy Cities and West China Research Center for Rural Health Development, Sichuan University, Chengdu, Sichuan Province, People’s Republic of China; 3Department of Maternal, Child and Adolescent Health, West China School of Public Health and West China Fourth Hospital, Sichuan University, Chengdu, Sichuan Province, People’s Republic of ChinaCorrespondence: Zhenmi Liu; Jay Pan Email zhenmiliu@scu.edu.cn; panjie.jay@scu.edu.cnAbstract: Competition has been widely introduced among hospitals in the hope of improving health-care quality. However, whether competition leads to higher-quality health care is a topic of considerable debate. We conducted a systematic review to assess the impact of hospital-market competition on unplanned readmission. We searched six electronic databases (PubMed, EmBase, Wiley Online Library, Web of Science, Scopus, and JSTOR) and reference lists of screened articles for relevant studies, and strictly followed methods proposed by the Cochrane Collaboration. Finally, nine observational studies with 2,241,767 patients were included. For the primary outcome, pooled results of three studies showed that it was uncertain whether or not hospital competition reduces readmission (β=0.02, P=0.06; very low certainty of evidence, as they were all observational studies with high heterogeneity). Inconsistent results were found in the remaining six studies, and they were assessed as very low–certainty evidence, downgraded for either inconsistency or indirectness or both. As for secondary outcomes, seven of the nine studies reported on the impact of competition on the risk of mortality, and two reported on length of stay (LOS). It was uncertain whether competition had an effect on mortality or LOS. The relevant studies were limited and of very low certainty, which means there is currently no reliable evidence showing that hospital competition reduces quality of health care in terms of readmission/mortality/LOS. There is a need for rigorous studies to assess the impact of hospital competition on the quality of health care.Keywords: hospital market, competition, readmission, quality of care, health policy